Inskripsi Melayu Sriwijaya - Coedes, G. (George); Metzger, Laurent, 1946-; Asmah Haji Omar, 1940- (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2009)
Study and interpretation of the inscriptions of Srivijaya Kingdom, ca. 7th century.
Includes bibliographical references (p. [89]-92)
In Malay
Keywords: Sanskrit literature -- History and criticism; Sanskrit literature -- History and criticism -- Translations into Malay